The growing impact of human papilloma virus (HPV)-associated cancers in men in Costa Rica: epidemiological and economic burden - Ospina-Henao, Sebastian; Brenes-Castillo, Francisco; Marcano-Lozada, Marcel; Betancur-Díaz, Maria Alejandra; Medina, Sebastian; Brenes-Chacon, Helena; Avila-Aguero, Maria L. (Frontiers in Public Health, 2025)
Human papillomavirus (HPV) is the most common sexually transmitted infection in men and women and is responsible for a substantial burden of disease worldwide. Although HPV-related disease burden is high in women due to cervical related disease and cancer, men are directly affected by HPV. According to the World Health Organization (WHO), one in three men has a prevalent HPV infection worldwide. Currently, there is a lack of data regarding the epidemiology and healthcare resource utilization (HCRU) of HPV-associated cancers among Costa Rican men. This study aimed to describe the epidemiological characteristics of HPV-associated male cancer and disease and the HCRU in Costa Rica. HPV-related cancers in men were assessed through retrospective database study for epidemiology and Delphi panel with five experts for HCRU. A total of 1,340 men with penile, anal, and head and neck cancers between 2012 and 2016 were identified in the database, with a mean age of 63.6 years. Anal cancer accounted for 48% of cases, followed by head and neck 44%, and penile cancer 11%. The cumulative rate of HPV-associated cancer in men per 100,000 population increased from 8.6 in 2012 to 55.5 in 2016. According to 4/5 panelists, resources for the disease management were also scarce. Panelists agreed that the cost for HPV management within their institution was 0.6–40,000 USD. Despite the increasing incidence e of HPV-related cancer in men, HPV prevention in men continues to be an under-served issue in public policy that could result in substantial economic and clinical burden. National health authorities should promote strategies to prevent HPV infections and associated diseases among Costa Rican men.